The Construction of the Pre Columbian Past as an Identity Element of the “Mexican” Territory, Through a Dialogical Dynamic Between Nueva España and the West, in the 17th and 18th Centuries - Muñoz Aréyzaga, Eréndira (2020)
The Mexican archaeological heritage is a tourist attraction, its construction depended on a historical process, intertwined with a search for identity elements to built a nation idea, based on its self and hetero recognition, along with the background of what we now consider archaeology. In order to know this process, a review of novohispano and western scientific texts about the pre-Columbian past, produced between the 17th and 18th centuries, that represent the process of its construction as an identity element, is presented. This process was mediated by the rationality that Enlightenment represented, the “leyenda negra” of Spain, and by Creole and Spanish nationalism. Thus, the realization of this historical process resulted from a dialogic dynamic between the New World and the West, because the politics and cultural conditions of both continents, facilitated the fact that they coincided in giving scientific production a nationalist use, which began to represent the Mexican nation internally and externally.